Spectroscopic Analysis of Selected Priority Trace Metals in the Extant East African Gilled Lungfish (Protopterus amphibius) in Lira Municipal Lagoon and Its Edibility Health Risk - Omara, Timothy; Ogwang, Remish; Ndyamuhaki, Sarah; Kagoya, Sarah; Kigenyi, Erisa; Musau, Bashir; Adupa, Eddie (Science Journal of Analytical Chemistry, 2018)
This investigation analyzed the concentrations of three trace metals in gilled lungfish of Lira Municipal lagoon of Lira District and estimated the health risk associated with its consumption. Three fresh lungfish samples from the down, middle and up sluices of the lagoon were caught, eviscerated, washed and sundried. Edible muscles of the samples were oven dried at 105°C, desiccated and pulverized. 2.0 ± 0.1g of the fine fish powders were ashed at 550°C, acid digested, and the filtrates used to prepare 1 litre sample solutions. The sample solutions were analyzed for Lead, Zinc and Cadmium by Atomic absorption spectrometry. Spectroscopic results showed that no Cadmium was detected while the statistical mean concentrations of Zinc and Lead in the fishes from down, middle and up streams in mg/kg were 157.8 ± 0.01, 160.2 ± 0.02, 158.2 ± 0.01 and 6.84 ± 0.01, 1.69 ± 0.03, 5.12 ± 0.01 respectively. The above results showed that the trace metals in the investigated fish samples are deleteriously above the maximum permissible Zinc (0.7mg/kg) and Lead (0.3mg/kg) levels in fish indicated by CODEX STAN 193-1995. The statistical Estimated Daily Intakes were from 26.27 to 26.66 mg/kg/day for Zinc and 0.28 to 1.48 mg/kg/day for Lead. A heightened Health Risk Index value of 88.67 for Zinc was observed in the middle stream lungfish samples while Lead had the lowest Health Risk Index value of 2.00 in the middle stream fish from the lagoon. All the Health Risk Index values were greater than unity except for Chromium that was undetected in the fish muscles thus the lungfish of the lagoon is unsafe for human consumption and continuous consumption will impact human health. The immediate strategy lies in fencing the lagoon area and putting a stringent restriction against fishing from the lagoon.
Keywords: Cadmium; Estimated Daily Intake; Lead; Health Risk Index; Target Hazard Quotient; Zinc